CAPITAL INTENSITY ON THE DETERMINANTS OF TAX AGGRESSIVENESS IN INDONESIA - Sholihah, Ria Anisatus; Fitriyani, Fitriyani (JEA17: Jurnal Ekonomi Akuntansi, 2024)
This research aims to determine the effect of leverage, the proportion of independent commissioners and institutional ownership on tax aggressiveness and to see whether capital intensity can moderate the relationship between leverage and tax aggressiveness, the proportion of independent commissioners with tax aggressiveness and institutional ownership on tax aggressiveness. This quantitative research uses secondary data sourced from the IDX. The data used are leverage ratio, the proportion of independent commissioners, institutional ownership, tax aggressiveness, and capital intensity in property and real estate companies listed on the IDX during 2018-2022. The research method uses multiple regression analysis and the MRA (Moderate regression analysis) test with the IBM SPSS Statistics 2. The research results show that the leverage ratio variable affects tax aggressiveness, while the proportion of independent commissioners and institutional ownership variables do not affect tax aggressiveness. Meanwhile, the results of the MRA test show that capital intensity can moderate the influence of leverage and the proportion of independent commissioners on tax aggressiveness, but capital intensity cannot moderate the influence of institutional ownership on tax aggressiveness.